A study on the quick measuring method of linear dynamic range of receiver. (January 2015) - Yao, Jinbao; Tang, Baoping; Zhao, Jie
Highlights: A quick measuring method for linear dynamic range measurement was proposed. The parametric division algorithm was used to optimize the sensitivity measurement. The translational iteration algorithm was constructed to accelerate PndB measurement. Abstract: This paper proposes a quick measuring method based on the parametric division algorithm and the translational iteration algorithm to solve the problem of large amounts of work and low efficiency of linear dynamic range measurement of receiver. The proposed method utilizes the parametric division algorithm to optimize the sensitivity measurement, then modifies the iteration algorithm and constructs the translational iteration algorithm to accelerate gain compression point measurement, and finally achieves the quick measurement of linear dynamic range. At last, an example of application is used to demonstrate the advantages of this method, i.e. less measuring procedures, quick speed, high efficiency, and optimum measuring accuracy.